Effect of leukocyte-platelet fibrin-rich wound reconstruction followed by full-thickness skin grafting in the treatment of diabetic foot Wagner grade 4 ulcer gangrene (toe area). (1st January 2023) - Wang, Yuqi; Wang, Yanyan; Wang, Xiaotao; Zhao, Yi; Ruan, Siyuan; Cao, Hong
Abstract: This study investigated the effect of L-PRF on promoting full-thickness skin grafting for the treatment of diabetic foot ulcer wounds and attempted to characterize the mechanism. In a retrospective study, we centrifugated 10–20 ml of venous blood at 1006.2 g for 20 min. The fibrin clot between the top oligocellular plasma layer and the bottom erythrocyte layer was extracted and directly used, without compression, to cover the wound after debridement. Patients who received L-PRF before skin grafting underwent surgery earlier than patients in the control group. Skin necrosis occurred in 7 patients (28%) in the L-PRF group and 16 (64%) in the control group. The difference was statistically significant, P < .05. The postoperative infection rate in the control group (56%) was significantly higher than that in the L-PRF group (24%), P < .05. During a mean follow-up of 1 year, ulcer recurrence occurred in 9 patients (36%) in the control group compared with 4 patients (16%) in the L-PRF group, P < .05. The final amputation rate was also higher in the control group (48%) than in the L-PRF group (20%). The difference is statistically significant, P < .05. The Maryland scale score and SF-36 score of the two groups of patients after treatment were significantly better than those before treatment, and the difference was statistically significant (P < .05). The L-PRF group (94.80 ± 4.14) had better foot scores at the last follow-up after treatment than the control group (88.84 ± 5.22) (P < .05). The results showed that L-PRF played a positive role in the treatment of Wagner grade 4 ulcer gangrene with free full-thickness skin grafts. P lain l anguage s ummary: What is the context? ● Diabetic foot is a serious complication in the later stage of the disease course of diabetic patients. The incidence rate is increasing year by year. In severe cases, it can lead to amputation or even death. ● For diabetic ulcer wounds, dressings such as L-PRF or autologous fat are often used in the initial stage to speed up wound healing. For advanced wounds, especially patients with local tissue gangrene, simple wound dressings cannot meet the needs of wounds. People often use skin flaps or different types of skin grafts to treat advanced wounds. ● Flap or skin grafting has been shown to be effective, but because of the patient's own neurovascular injury and infection, the rate of graft necrosis and ulcer recurrence is extremely high. What is new? ● This study discusses the treatment of advanced wounds in diabetes. After thorough debridement and before skin grafting, we first covered the wound with L-PRF and observed the wound condition. Studies have shown that the use of L-PRF can allow the original poor wound to be reconstructed: the content of growth factors and growth-related cells is increased, blood circulation is improved and granulation tissue growth, bone and tendon exposure is improved, and infection is controlled. What is the impact? ● This study provides evidence that using L-PRF to reconstruct wounds can greatly shorten the preparation time for elective surgery. Reconstructed wounds can better accept free skin grafts, and the incidence of postoperative complications and amputation (particularly, toe amputation) is also lower.